PENGEMBANGAN APLIKASI UMKM GO ONLINE PADA PEKON BANDUNGBARU BARAT - Muhammad Junaidi; Trisnawati Trisnawati; Kasmi Kasmi; Wulandari Wulandari; Rulin Suastika; Sri Ipnuwati (LP3K Lampung, 2022)
The development of information in society is still a lot that is less effective, efficient, and actual. Even in Indonesia, information hoaxed or cannot be trusted is often developed. This is common in various sectors of society, even MSMEs (Micro, Small and Medium Enterprises) regarding the invalidity of places, business actors, types of businesses, and information related to this which is still unclear. For this reason, the goal is to hold a special information forum in the form of a non-prepaid application in the hope that it can contain information according to the truth. And also this MSME application can help local communities and also people outside West Bandung Baru to find out the types of micro-businesses that exist in West Bandung and West Bandung Villages. The team also hopes that this application can support all types of micro-businesses to be more competent and advanced in the future. This study uses pretest and posttest to determine the effectiveness of the training activities and application development that have been carried out. Based on the results of the pretest and posttest that have been carried out, it can be concluded that there is an increase in the understanding of MSME actors regarding online marketing.